How can we get more reliable information from homoeopathic pathogenetic trials? - Dantas, Flávio (British Homeopathic Journal, 1996)
Indeed, a medicine must first of all be essayed in a healthy body, without any foreign admixture; when the odour and taste have been examined, a small dose must be taken, and attention must be paid to every change that occurs, to the pulse, the temperature, respiration and excretions. Then, having examined the symptoms encountered in the healthy person, one may proceed to trials in the body of a sick person.